Anogenital Crohn's Disease and Granulomatosis: A Systematic Review of Epidemiology, Clinical Manifestations, and Treatment. (20th November 2021) - Honap, Sailish; Meade, Susanna; Spencer, Ashley; Pavlidis, Polychronis; Luber, Raphael P; Calonje, Eduardo; Rashidghamat, Ellie; Bunker, Christopher B; Lewis, Fiona; Irving, Peter M
Abstract: Background and Aims: Metastatic Crohn's disease is an extraintestinal cutaneous manifestation characterised by non-specific inflammatory lesions anatomically separate from the gut; genital involvement is rare. We conducted a systematic review of anogenital Crohn's disease and granulomatosis, to provide a synthesis of epidemiology, clinical features, and treatment outcomes. Methods: A systematic search of the literature was conducted via MEDLINE, EMBASE, and the Cochrane database from inception to December 1, 2020. Two investigators extracted and analysed study data. Response and remission were defined as partial improvement or complete resolution of symptoms and examination findings, respectively. Results: Of 9381 screened studies, 185 articles, [410 cases: 273 female, 137 male] were included. The predominant clinical features were oedema, ulcers, fissures, and hypertrophic lesions. Adults and children present similarly. Luminal Crohn's disease was diagnosed in nearly 80% of cases including 45–80% patients without gastrointestinal symptoms (time to inflammatory bowel disease [IBD] from anogenital Crohn's disease diagnosis [range] –43 to 11 years). Antibiotics, corticosteroids, thiopurines, and anti-tumour necrosis factor [TNF] therapy were the most frequently prescribed agents. At final follow-up, non-response, response, and remission rates were 37/304 [12%], 267/304 [88%], and 114/304 [38%], respectively. Oedema was associated with a poor response to topical therapy. Greater response rates to anti-TNF therapy were seen in patients prescribed concomitant immunomodulation [24/25, 96% vs 67/90, 74%, p = 0.02]. Conclusions: We provide an illustrative summary of the clinical presentation and treatment effectiveness of this rare, under-recognised condition, and a proposed algorithm for approach and management. Prospective studies with longer follow-up are required to define optimal treatment strategies.